EDUKASI PEMANFAATAN BAHAN ALAM SEBAGAI OBAT TRADISIONAL UNTUK PENCEGAHAN PENYAKIT DAN PERAWATAN KESEHATAN - Fatiha Khairunnisa; Qurrota A’yuni; Kautsar Ul Haq; Harsasi Setyawati; Ahmadi Jaya Permana; Rico Ramadhan; Yanuardi Raharjo; Mulyadi Tanjung; Sri Sumarsih; Hartati; Handoko Darmokoesoemo (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
One of the ways to maintain the personal health during an emergency condition as the current COVID-19 is the utilization of natural ingredients. It can be processed into traditional medicines. Jamu as a type of traditional medicine as well as natural heritage has been widely used by Indonesian to prevent the body from disease and to treat the health issue. This community service aimed to provide education for society regarding the chemical content and efficacy of natural ingredients such as empon-empon. The techniques to process it into traditional medicine for family healthcare was also delivered. The activity was carried out through face-to-face meeting while still applying the health protocols. The level of success and usefulness of the activity was known from the response of the participants. In general, the PKM activities in the scheme of theory and practical session has been carried out well. The materials presented in theory session was understandable. Meanwhile, the techniques used in practical session was easy to be replicated. The activity was expected to increase the knowledge and skills of the society in terms of natural ingredients that have good chemical content and the techniques to process them into nutritious drinks for families.